A7.23 The HLA Locus Contains Novel Foetal Susceptibility Alleles for Congenital Heart Block with Significant Paternal Influence. (25th February 2013) - Görgen, Sabrina; Östberg, Therese; Salomonsson, Stina; Ding, Bo; Eliasson, Håkan; Mälarstig, Anders; Alfredsson, Lars; Klareskog, Lars; Hamsten, Anders; Olsson, Tomas; Axelsson, Tomas; ,; et al.
Abstract : Objective: To identify foetal susceptibility genes in Ro/SSA autoantibody-mediated congenital heart block on chromosome six. Methods: Single nucleotide polymorphism (SNP) genotyping of individuals included in the Swedish Congenital Heart Block (CHB) study population was performed. Low resolution HLA-A, -Cw and -DRB1 allele typing was carried out in 86 families of the study population comprising 339 individuals (86 Ro/SSA autoantibody positive mothers, 71 fathers, 87 CHB index cases and 95 unaffected siblings). Results: A case-control comparison between index cases and population-based out of study controls (n = 1710) revealed an association of CHB with fifteen SNPs in the 6p21.3 MHC locus at a chromosome-wide significance of p < 2.59 × 10 –6 (OR 2.21–3.12). In a family-based analysis between SNP markers as well as distinct MHC class I and II alleles with CHB we observed associations to HLA-DRB1*04 and HLA-Cw*05 variants that were significantly more often transmitted to affected individuals (p < 0.03 and p < 0.05, respectively), and HLA-DRB1*13 and HLA-Cw*06 variants which were significantly less often transmitted to affected children (p < 0.05 and p < 0.04). We further observed a significant association of increased paternal, but not maternal, HLA-DRB1*04 transmissions to the affected offspring (p < 0.02). Conclusions: Our study identifies HLA-DRB1*04 and HLA-Cw*05 as novel foetal HLA-allele variants that confer susceptibility to develop CHB in response to exposure to Ro/SSA autoantibodies, while DRB1*13 and Cw*06 emerged as protective alleles. For the first time, we also demonstrate paternal contribution to foetal susceptibility to CHB.